2016
DOI: 10.24278/2178-5031.201628204
|View full text |Cite
|
Sign up to set email alerts
|

Epífitas Vasculares Do Parque Estadual De Porto Ferreira, São Paulo, Brasil

Abstract: O Parque Estadual de Porto Ferreira – PEPF já foi alvo de diversos estudos florísticos, contudo, nenhum deles inventariou exclusivamente a flora epifítica vascular. Neste estudo realizamos o levantamento florístico das epífitas vasculares nos diferentes tipos de vegetação desta Unidade de Conservação e comparamos a similaridade florística com outras localidades do interior do Estado de São Paulo, em Floresta Estacional Semidecidual, Cerradão e florestas ribeirinhas. Na área, foram inventariadas as epífitas vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, even in the Cerrado forestry vegetation type, the herbaceous layers must be considered as an important synusia. On the other hand, the high number of exclusive herbaceous species in the RP must be attributed to the microclimatic conditions propitious to the epiphytes' development (Marcusso et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, even in the Cerrado forestry vegetation type, the herbaceous layers must be considered as an important synusia. On the other hand, the high number of exclusive herbaceous species in the RP must be attributed to the microclimatic conditions propitious to the epiphytes' development (Marcusso et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The PFSP vascular flora checklist was created from the following: specimens collected by the authors from 2014 to 2017, using the walking research method (Filgueiras et al, 1994); the systematization of all other lists found in surveys carried out in PFSP (Bertoni, 1984;Bertoni & Martins, 1987;Bertoni et al, 2001;São Paulo, 2003;Colli et al, 2003;Oliveira, 2012;Osaco, 2012;Dickfeldt et al, 2013;Sabino, 2013;Konopczyk, 2014;Marcusso et al, 2016;Vargas et al, 2018); and the compilation of vouchers present in the Specieslink database (CRIA, 2019). We considered only native taxa identified at the taxonomic level of species and excluded those with dubious identification, at the genera-level and exotic species (cited in a separate table -Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in soil properties among phytophysiognomies on different geological surfaces in the vegetation complex of Campo Maior in the ecotonal region of the Parnaíba basin in the state of Piauí continuous ferruginous and lateritic concretions is of common occurrence and affects effective rooting depth and causes changes in phytophysiognomies (Barros & Castro 2006). The basin of Parnaiba is characterized by the presence of fragments of cerrado, caatinga and forests in a mosaic of ecotonal vegetations with characteristic flora e structural features, conditioned by local edaphic factors (Barros et al 2010;Barros & Castro 2006;Rossi et al 2005).…”
Section: Harmony Of Knowledge Exploring Interdisciplinary Synergiesmentioning
confidence: 99%